2022
DOI: 10.7759/cureus.21230
|View full text |Cite
|
Sign up to set email alerts
|

Niemann-Pick Type B: A Rare Cause of Interstitial Lung Disease

Abstract: Niemann-Pick disease (NPD) is a rare lysosomal storage disease (LSD) with multisystemic involvement. The disease is heterogeneous and classified into three subtypes: type A and B result from deficient acid sphingomyelinase activity and leads to the accumulation of sphingomyelin and type C is a genetically different disease resulting from defective intracellular trafficking of cholesterol with accumulation of glycosphingolipids. Type A is generally a neurodegenerative disease and is fatal in infancy. Type B is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Niemann-Pick disease is an uncommon autosomal recessive inherited disease which could affect multiple organs including liver, spleen, lung and other macrophage-abundant organs ( 13 ). Previous reports of NPD type B cases showed that interstitial lung lesions are common ( 14 ). The girl’s X-ray showed interstitial changes leading to CO 2 retention, which may explain the respiratory acidosis.…”
Section: Discussionmentioning
confidence: 96%
“…Niemann-Pick disease is an uncommon autosomal recessive inherited disease which could affect multiple organs including liver, spleen, lung and other macrophage-abundant organs ( 13 ). Previous reports of NPD type B cases showed that interstitial lung lesions are common ( 14 ). The girl’s X-ray showed interstitial changes leading to CO 2 retention, which may explain the respiratory acidosis.…”
Section: Discussionmentioning
confidence: 96%
“…In the lungs, excess sphingomyelin accumulation in alveolar macrophages impairs their normal function, causing a buildup of surfactant lipids and proteins in the alveoli known as pulmonary alveolar proteinosis (3,10). The alveoli become filled with lipoproteinaceous material, impairing gas exchange and causing respiratory symptoms that can ultimately lead to respiratory failure if untreated due to impaired diffusion capacity and ventilation-perfusion mismatch (10)(11)(12)(13).…”
mentioning
confidence: 99%